Concordance of DLQI and pain score in hidradenitis suppurativa clinical trials: a systematic review - Adina Greene, BA; Angelina S. Hwang, MD; Sarah Amjad, BS; Jacob A. Kechter, MD; Aaron R. Mangold, MD; Stella X. Chen, MD (International Journal of Women's Dermatology, 2025)
Background:. Hidradenitis suppurativa (HS) is a chronic, recurrent inflammatory condition and is associated with significant psychosocial impacts on patient quality of life. Objective:. This study aimed to characterize the utilization of patient-reported outcomes (PROs) in HS clinical trials and their concordance with trial primary endpoints. Methods:. A systematic review of clinical trials was performed using the publicly available U.S. National Library of Medicine (ClinicalTrials.gov) in June 2023 utilizing the search terms hidradenitis, hidradenitis suppurativa, and suppurativa hidradenitis. Study title, start year, trial status, intervention, design, location, and primary and secondary outcomes were collected. To assess for concordance of patient and provider-reported outcomes, we identified published placebo-controlled trials that included Dermatology Life Quality Index (DLQI) and/or a numeric rating scale (NRS) for pain, the 2 most utilized PROs. Results:. One hundred sixty-four HS clinical trials were identified, of which 115 were interventional studies. A total of 65.2% (n = 107) of HS trials included at least one PRO. Pain NRS (42.7%, n = 70) and DLQI (42.1%, n = 69) were the most frequently used PRO instruments. The use of PROs in clinical trials increased over time, with 50% of trials between 2020 and 2023 utilizing PROs. Of 11 published HS trials, 82% (n = 9) trials showed concordance of provider-assessed and PROs in at least one treatment arm. Limitations:. Significance and standard deviations of PROs were rarely reported, preventing the calculation of significance and is a limitation of this review. Conclusion:. While lesion counts provide single snapshots of disease, PROs can capture perceptions of lesions not actively present. PROs are frequently concordant with both achievement and nonachievement of primary endpoints in clinical trials.